Early Visions and Representations of America: Álvar Núñez Cabeza de Vaca’s ’Naufragios’ and William Bradford’s ’Of Plymouth Plantation’ - Sylvia L. Hilton (Miscelánea: A Journal of English and American Studies, 2015)
.